Peran Masjid Al-Hikmah dalam Dinamika Kehidupan Masyarakat Desa Gunung Agung Kabupaten Lahat - Shafira Putri Setiaji; Sekar Asih; Rizca Dini Amalya; Hudaidah Hudaidah; Tyas Fernanda (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2026)
This study is to investigate the significance of Al-Hikmah Mosque in the community of Gunung Agung Village, West Merapi District, Lahat Regency. This study examines the mosque's dual role as a site of worship and a hub for social and educational activity within the rural community. This study employs a qualitative methodology with descriptive techniques to acquire a comprehensive understanding of social reality. Data were gathered via interviews with the mosque imam and community leaders, observations of activities occurring at the mosque, and an examination of literature pertinent to the research issue. The study's findings indicate that Al-Hikmah Mosque serves multiple functions, including the conduct of regular worship such as congregational prayers and Islamic holidays, the facilitation of informal educational activities like Quran recitation lessons for children, and as a venue for deliberation on social issues. In traditions that have evolved since its inception as a modest mosque in 1952. Consequently, the Al-Hikmah Mosque has substantially enhanced the spiritual life, social cohesion, and harmony of the Gunung Agung Village community. Furthermore, the mosque embodies the principles of unity and the perpetuation of religious traditions that have evolved since its inception as a modest mosque in 1952. Consequently, the Al-Hikmah Mosque has substantially enhanced the spiritual life, social cohesion, and unity of the Gunung Agung Village community.